Power potential of separate types of alternative fuel and estimation of power inputs on their preparation for direct incineration in steam generating units - Bilodid V.D.; Kuts G.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2011)
An analysis is conducted and the estimation of possible power potential of separate alternative types of fuel is given, direct expenses of energy supply on their booty, production and preparation to incineration in steam generating units. The followings types of fuel are considered: peat, wastes of the timber cuttings, agricultural biomass, mine methane.General power potential of the indicated types of fuel after a separate variant makes 9360 thousands of conditional fuel, including peat is a piece – 1700, wastes of wood – 1700, straw of corn cultures – 3800, mine methane – 1000.Direct expenses of energy supply on a booty and preparation of alternative types of fuel resulted to 1 kg of conditional fuel, followings: peat is a piece are 23,9 kg of conditional fuel, peat milling – 49,7; peat briquettes – 143,5; straw in bales – 31,0; straw in briquettes – 170; straw in granules – 238,3; wood on condition of its gasification – 240,8; mine methane – 151,0. Got values of direct power expenses on preparation of alternative fuels to incineration except for peat of piece exceed analogical indexes for the traditional types of fuel.